ENTOMOPATHOGENIC BACTERIUM Serratia marcescens ISOLATED FROM Episparis tortuosalis CAUSING A DAMAGE TO Chukrasia tabularis IN VIETNAM - Duy Long, Pham; Bao Thanh, Le; Xuan Hung, Tran; Thi Hang, Hoang; Tien Tai, Dinh; Van Phuc, Phuong; Duc Long, Bui; Minh Chi, Nguyen (Journal of Forestry Science and Technology, 2023)
Episparis tortuosalis Moore, 1867 is a serious pest of the Chukrasia tabularis A. Juss which is widely planted in plantations in Vietnam. A biocontrol option to manage this pest is a priority for the forest sector. The objective of this study was to evaluate whether there are potential biocontrol candidates within the E. tortuosalis population. Sixteen bacterial strains were isolated from E. tortuosalis larvae that were parasitized in a C. tabularis plantattion in Nghe An province. Four isolates (FPRC06, FPRC07, FPRC14 and FPRC16) had strongest pathogenicity on Galleria mellonella larvae at 1, 24 and 36 hours after the injection and 72, 96 and 120 hours after the spraying experiments. The mortality rate of G. mellonella resulted from these two experimental approaches at the end of experiments was 93.3–100% and 76.7–100%, respectively. In a greenhouse experiment, the four isolates caused 44.3–61.1%, 52.0–68.0%, 54.3–69.1% and 41.4–60.7% mortality of E. tortuosalis larvae after 3, 5 and 7 days of spraying, respectively. These results were similar to applying a commercial Bacillus thuringiensis. The two isolates (FPRC07, FPRC14) were identified as Serratia marcescens based on phylogenetic analysis of 16S rRNA. Thus, this finding reveals the potential opportunities for the development of a natural insecticide of E. tortuosalis in Vietnam.